Pengaruh Dampak Arus Kas Operasi dan Laba Terhadap Return Saham dan Dividen Kas Pada Perusahaan Industri Dasar & Kimia Yang Terdaftar Di Bursa Efek Indonesia - Sahmia Munthe; Tika Indria; Jalilah Ilmiha (Universitas Islam Islam Sumatera Utara, 2022)
The purpose of this study is to empirically examine the effect of operating cash flow and earnings on stock returns and cash dividends/cash dividends. This study uses the independent variables, namely operating cash flow and profit, and the dependent variable is stock returns and cash dividends. The research sample was taken from basic chemical industrial companies listed on the Indonesian stock exchange. Sampling was done by using purposive sampling method. The data collected is secondary data from the official website of the Indonesia Stock Exchange and the company's annual financial reports on their respective official websites. The data analysis method used is the classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test. Multiple linear regression test, partial and simultaneous hypothesis testing, and coefficient of determination test. The results of this study indicate that partially operating cash flow has no significant effect on stock returns and cash dividends, and earnings have a significant effect on stock returns and cash dividends. Meanwhile, simultaneously operating cash flow and significant profit on stock returns and cash dividends.A B S T R A C T The purpose of this study is to empirically examine the effect of operating cash flow and earnings on stock returns and cash dividends/cash dividends. This study uses the independent variables, namely operating cash flow and profit, and the dependent variable is stock returns and cash dividends. The research sample was taken from basic chemical industrial companies listed on the Indonesian stock exchange. Sampling was done by using purposive sampling method. The data collected is secondary data from the official website of the Indonesia Stock Exchange and the company's annual financial reports on their respective official websites. The data analysis method used is the classical assumption test consisting of normality test, multicollinearity test, and heteroscedasticity test. Multiple linear regression test, partial and simultaneous hypothesis testing, and coefficient of determination test. The results of this study indicate that partially operating cash flow has no significant effect on stock returns and cash dividends, and earnings have a significant effect on stock returns and cash dividends. Meanwhile, simultaneously operating cash flow and significant profit on stock returns and cash dividends.